New Insights Into the Physiopathology of COVID-19: SARS-CoV-2-Associated Gastrointestinal Illness - Devaux, Christian A.; Lagier, Jean-Christophe; Raoult, Didier (Frontiers in Medicine, 2021)
Although SARS-CoV-2 is considered a lung-tropic virus that infects the respiratory tract through binding to the ACE2 cell-surface molecules present on alveolar lungs epithelial cells, gastrointestinal symptoms have been frequently reported in COVID-19 patients. What can be considered an apparent paradox is that these symptoms (e.g., diarrhea), sometimes precede the development of respiratory tract illness as if the breathing apparatus was not its first target during viral dissemination. Recently, evidence was reported that the gut is an active site of replication for SARS-CoV-2. This replication mainly occurs in mature enterocytes expressing the ACE2 viral receptor and TMPRSS4 protease. In this review we question how SARS-CoV-2 can cause intestinal disturbances, whether there are pneumocyte-tropic, enterocyte-tropic and/or dual tropic strains of SARS-CoV-2. We examine two major models: first, that of a virus directly causing damage locally (e.g., by inducing apoptosis of infected enterocytes); secondly, that of indirect effect of the virus (e.g., by inducing changes in the composition of the gut microbiota followed by the induction of an inflammatory process), and suggest that both situations probably occur simultaneously in COVID-19 patients. We eventually discuss the consequences of the virus replication in brush border of intestine on long-distance damages affecting other tissues/organs, particularly lungs.